Exploiting the unique properties of nanobodies: enhancing therapeutics, drug delivery, and targeted diagnostics - Blank, Lisa; Pander, Giulia; Mühlberg, Eric; Mier, Walter; Uhl, Philipp (Drug discovery today, 2025)
Nanobodies (Nbs) are genetically engineered single domain antibodies derived from heavy chain-only antibodies (HcAbs) found in camelid species. These monomeric antibody fragments are smaller and have lower molecular weight compared with conventional antibodies, while retaining full antigen-binding specificity, endowing them with unique structural and functional properties. As in vitro diagnostics, they can aid pathogen detection and biomarker identification. In vivo, their rapid clearance and deep tissue penetration enable radio-imaging with short half-life radionuclides, reducing patient exposure. Therapeutically, Nbs are being explored for cancer, neurodegenerative, and infectious diseases. However, their short serum half-life is challenging, prompting strategies to extend circulation time without compromising their benefits. Despite these hurdles, the high specificity, low immunogenicity, and versatility of Nbs position them as promising tools across diverse applications.
Online verfügbar: 1. November 2025, Artikelversion: 17. November 2025
Gesehen am 26.01.2026